Trends in liver transplantation for primary biliary cholangitis in Europe over the past three decades. Issue 3 (18th December 2018) - Harms, Maren H.; Janssen, Quisette P.; Adam, Rene; Duvoux, Christophe; Mirza, Darius; Hidalgo, Ernest; Watson, Christopher; Wigmore, Stephen J.; Pinzani, Massimo; Isoniemi, Helena; Pratschke, Johann; Zieniewicz, Krzysztof; et al.
Summary: Background: The importance of primary biliary cholangitis as an indication for liver transplantation has probably been influenced by the introduction of therapies, and changes in selection criteria and disease epidemiology. Aims: To assess the time trends in liver transplantation for primary biliary cholangitis and to evaluate the characteristics of the patient population during the past three decades. Methods: Patients undergoing liver transplantation from 1986 to 2015 in centres reporting to the European Liver Transplantation Registry were included. We excluded combined organ transplantations and patients <18 years. Trends were assessed using linear regression models. Results: We included 112 874 patients, of whom 6029 (5.3%) had primary biliary cholangitis. After an initial increase in the first decade, the annual number of liver transplantation for primary biliary cholangitis remained stable at around 200. The proportion of liver transplantations for primary biliary cholangitis decreased from 20% in 1986 to 4% in 2015 ( P  < 0.001). Primary biliary cholangitis was the only indication showing a consistent proportional decrease throughout all decades. From the first to the third decade, the age at liver transplantation increased from 54 (IQR 47‐59) to 56 years (IQR 48‐62) and the proportion of males increased from 11% to 15% (both P  < 0.001). Conclusions: We have found a proportional decrease in primary biliary cholangitis as indication for liver transplantation. However, despite treatment with ursodeoxycholic acid and improved disease awareness, the absolute annual number of liver transplantations has stabilised.